Surgical removal of subfoveal perfluorocarbon liquid using combined flute needle and vacuum aspiration in silicone oil-filled eyes: A novel technique to remove subfoveal PFCL - Pan, Qintuo (Indian J Ophthalmol, 2018)
We report a procedure using a pressure-controllable flute needle to remove subfoveal retention of perfluorocarbon liquid (PFCL) under silicone oil. With a two-port pars plana approach, we used a 27-gauge dental injection needle to create a retinotomy at the farthest edge of the PFCL bubble from the fovea. A 27-gauge flute needle was then inserted into the edge of the subfoveal PFCL to aspirate it with vacuum pressure. Three patients with subfoveal retained PFCL were treated by this procedure within silicone oil tamponade 1 month after the first operation. They promptly underwent successful removal of the PFCL with postoperative retinal reattachment and good visual outcome. This procedure allows safe and early treatment for subfoveal retained PFCL. Many medical institutions around the world could implement this procedure using common dental injection needles and flute needles.